Hydrogen desorption kinetics of MgH2 synthesized from modified waste magnesium - Figen, Aysel Kanturk; Coskuner, Bilge; Piskin, Sabriye (SCIENDO, 2014)
In the present study, hydrogen desorption properties of magnesium hydride (MgH2) synthesized from modified waste magnesium chips (WMC) were investigated. MgH2 was synthesized by hydrogenation of modified waste magnesium at 320 degrees C for 90 min under a pressure of 6 x 10(6) Pa. The modified waste magnesium was prepared by mixing waste magnesium with tetrahydrofuran (THF) and NaCl additions, applying mechanical milling. Next, it was investigated by X-ray diffraction (XRD), X-ray fluorescence (XRF), scanning electron microscopy (SEM) and Brunauer-Emmett-Teller (BET) techniques in order to characterize its structural properties. Hydrogen desorption properties were determined by differential scanning calorimetry (DSC) under nitrogen atmosphere at different heating rates (5, 10, and 15 degrees C/min). Doyle and Kissenger non-isothermal kinetic models were applied to calculate energy (E-a) values, which were found equal to 254.68 kJ/mol and 255.88 kJ/mol, respectively.
Keywords: hydrogen desorption; magnesium hydride; kinetics; waste magnesium chips; STORAGE PROPERTIES; COMPOSITES; GRAPHITE; SORPTION; DEHYDROGENATION; ADDITIVES; BEHAVIOR; ALLOY; Materials Science